Evaluation of HIV1 GP 120-CD4 Binding Inhibition Potentials of the Stem Bark Extracts of Diospyros mespiliformis - Mohammed, B.; Abba, S.A.; Gali, S. (UMYU Journal of Microbiology Research)
The study was conducted to evaluate the HIV1 gp120-CD4 binding inhibitory potential of crude aqueous, methanol and petroleum ether extracts of Diospyros mespiliformis. The extracts were obtained by Soxhalet extraction. Phytochemical screening, gp120-CD4 binding inhibitory potential, and sub-acute toxicity tests were carried out using standard techniques. Total of six phyto-constituents were identified in the extracts; flavonoids, alkaloids and balsams in aqueous extract, while flavonoids, alkaloids, tannins, balsams, steroids and cardiac glycosides in methanol extract, and flavonoids, alkaloids in the petroleum ether extract. Mean percentage inhibitions of the extracts of Diospyros mespiliformis against HIV-1 gp120-CD4 binding were recorded at various concentrations of the extracts, with 10% inhibition was recorded at 125µg/ml in aqueous extract, 13% and 18% inhibitions were recorded at 250 and 125µg/ml in methanol extract respectively, while 3% inhibition was found in 125µg/ml of petroleum ether extract respectively. Physical signs of toxicity; weight changes, hair loss, diarrhea, and weakness of the body of the laboratory animals treated with 250 and 125mg/kg were observed. There was no significant difference (P>0.05) in serum Aspartate Amino Transferase (AST) and Alkaline Phosphatase (ALP). There were no signs of Inflammation observed in the tissues of animals treated with all the extracts. It can be concluded that the methanol extracts possessed higher anti gp120-CD4 binding activity and extracts were non- toxic to the animals.